Job Satisfaction as an Interventing Variable in The Relationship Between Leadership and Organizational Culture and Employee Performance - Nurlela Talaohu; Abdul Hadi Sirat; Marwan Marwan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to determine the influence of leadership and organizational culture on employee performance through job satisfaction as a mediator. The total population is 45 employees, so this study is a population study, where the entire population is used as respondents. Data collection was carried out by distributing questionnaires to all respondents. The analysis technique used in this study is path analysis with the help of SPSS 25 windows application. The hypothesis test results found that leadership had a significant negative effect on employee performance, while organizational culture and job satisfaction had a significant positive effect on employee performance. Leadership and organizational culture have a positive and significant effect on job satisfaction. In addition, the results of the mediation test show that job satisfaction can mediate the influence of leadership and organizational culture on employee performance.